Construction of an isokinetic horizontal eccentric towing device to improve sprinting performance. (March 2021) - Tinwala, Farhan; Haemmerle, Enrico; Cronin, John; Ross, Angus
Horizontal eccentric towing (HET) is a novel modality that delivers an eccentric overload to the musculature as an athlete attempts to move forward in a sprint stance whilst being pulled backwards. A device, called the HET, has been developed to automate this movement. Similar to a winch retracting an anchor on a boat, the HET device pulls an athlete that is tethered inwards and the athlete must resist this motion in a maximal manner, whilst maintaining a sprint stance. The HET device provides an isokinetic training modality by towing athletes inwards at a constant velocity. The HET device is operated by an electric 10 kW AC synchronous servo gearmotor. The motor is controlled by a variable speed drive (VSD) and programmable logic controller (PLC), which allow for accurate speed, position and torque control. A touchscreen PC runs the user interface displaying real-time force and speed measures. The HET device can produce a maximum towing force of 2.8 kN at ground velocities of up to 3.58 m/s. There is a separate safety PLC that triggers a safety-rated brake system when the E-stop buttons are pushed. This is paramount for athlete safety. In this technical note, the components used in the construction of the HET device will be detailed and insights into a novel stimulus will be offered, as well as a guide to develop and automate similar eccentric movements.